Rechargeable nickel–iron batteries for large-scale energy storage - Abdalla, Abdallah H; Oseghale, Charles I; Gil Posada, Jorge O; Hall, Peter J (IET renewable power generation, 2016)
This study reports the effect of iron sulphide and copper composites on the electrochemical performance of nickel–iron batteries. Nickel stripes were coated with an iron-rich electroactive paste and were cycled against commercial nickel electrodes. The electrodes electrochemical and physical characterisation were carried out by using galvanostatic charge/discharge, cyclic voltammetry, X-ray diffraction, and atomic force microscopy techniques. The authors’ experimental results would indicate that the addition of iron sulphide and copper (II) sulphate significantly enhances the performance of the battery. Their in-house made iron-based electrodes exhibit good performance, with great potential for grid energy storage applications.